2022
DOI: 10.1002/cbin.11975
|View full text |Cite
|
Sign up to set email alerts
|

Lactate: a pearl dropped in the ocean—an overlooked signal molecule in physiology and pathology

Abstract: Lactate, once recognized as a wasty product from anaerobic glycolysis, is proved to be a pivotal signal molecule. Lactate accumulation occurs in diverse physiological and pathological settings due to the imbalance between lactate production and clearance. Under the condition with drastic changes in local microenvironment, such as tumorigenesis, inflammation, and microbial infection, the glycolysis turns to be active in surrounding cells leading to increased lactate release. Meanwhile, lactate can be utilized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…The hallmark of chronic wounds is matrix metalloproteinase (MMP) overactivity, the use of acidic wound dressings to shift from a high alkaline pH to a low alkaline pH in chronic wounds may reduce MMP activity and promote the transition from the inflammatory to the proliferative phase and angiogenesis (Trengove et al, 1999). Lactate, initially considered a metabolic waste product, has been studied and shown to regulate changes in the wound microenvironment thereby promoting wound healing (Wu et al, 2023). It has been reported that the accumulation of lactate in the organism reduces the pH of the alkaline environment caused by reduced carbon dioxide and elevated oxygen tension, allowing cells that favor wound healing to proliferate and differentiate within the appropriate physiological pH range (DeBerardinis & Chandel, 2020).…”
Section: Lactate In the Wound Microenvironmentmentioning
confidence: 99%
“…The hallmark of chronic wounds is matrix metalloproteinase (MMP) overactivity, the use of acidic wound dressings to shift from a high alkaline pH to a low alkaline pH in chronic wounds may reduce MMP activity and promote the transition from the inflammatory to the proliferative phase and angiogenesis (Trengove et al, 1999). Lactate, initially considered a metabolic waste product, has been studied and shown to regulate changes in the wound microenvironment thereby promoting wound healing (Wu et al, 2023). It has been reported that the accumulation of lactate in the organism reduces the pH of the alkaline environment caused by reduced carbon dioxide and elevated oxygen tension, allowing cells that favor wound healing to proliferate and differentiate within the appropriate physiological pH range (DeBerardinis & Chandel, 2020).…”
Section: Lactate In the Wound Microenvironmentmentioning
confidence: 99%
“…We reasoned that the nanomicelles could circulate for a long period due to the improved stability, bulky size, and reduced immunogenicity, resulting in improved tumor accumulation. Since the tumor microenvironment is slightly acidic (extracellular pH: 6.4–7.1), the nanomicelles should dissociate into positively charged unimers to adsorb onto the tumor cell surface to trigger the transcytosis of CAT-PEPA, leading to enhanced tumor penetration and thus efficient hypoxia reversion.…”
Section: Introductionmentioning
confidence: 99%
“…Since the tumor microenvironment is slightly acidic (extracellular pH: 6.4−7.1), 30 the nanomicelles should dissociate into positively charged unimers to adsorb onto the tumor cell surface to trigger the transcytosis of CAT-PEPA, leading to enhanced tumor penetration and thus efficient hypoxia reversion.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades there has been growing recognition that lactate, the end product of glycolysis, serves many functions, including acting as a source of energy, a signaling molecule, and even as an epigenetic regulator. The high metabolic demands of the brain and the numerous roles of lactate in CNS function have been extensively discussed elsewhere [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%